Analysis of the Qaulan Concept in the Qur'an as a Communication Model for Educators and Learners - Hilda Ainissyifa; Dindin Jamaluddin; Fajar Farham Hikam; Ika Kusuma Nindyah (UIN Sunan Gunung Djati Bandung, 2022)
The effectiveness of an educator with his students in this learning depends on how effectively the communication is used, That's why this communication becomes a determinant of whether a student can receive and process information or not. Besides, many problems students who deal with behavioral (psychological) disciplines, can be solved by effective mutual communication with the teacher. The purpose of this research is the formation of a communication model between educators and students in accordance with the concept of the seven qaulan contained in the verses of the Qur'an which are carried out with a communication approach. The method in this research is the method of qualitative approach, using library research. In its implementation, researchers also use the maudhu'i or thematic interpretation method by collecting verses containing the word qaulan in the form of the target object, then examine on aspects of therapeutic communication.Â The results of this study are several models of educator communication and students, including: first, the concept of qaulan karima and qaulan tsaqila become a basic principle in communication; second, the concept of qaulan sadida becomes a model of an educator's self-analysis before communicating; third, the concept of qaulan ma'rufa and qaulan baligha become models of educator attitudes and appearances in communicating; Fourth, the concept of qaulan maysura becomes a process stage communicating educators; Fifth, the concept of qaulan layyina becomes an educational technique in communicating.